Obstacle course: the everyday struggle to get an abortion in America - Cohen, David S. (University of California Press, 2020)
Introduction: the turbulent state of abortion in America -- Making the decision: coping with roadblocks, deception, and lies -- Finding and getting to a clinic: hard to find, harder to reach -- Coming up with the money -- Getting in: medical clinics as war zones -- Counseling at the clinic: government-mandated deceit -- Waiting periods: logistical nightmares, potentially serious delays -- The procedure: politics overrides medical expertise -- An alternate vision: abortion as normal healthcare.